2023
DOI: 10.1039/d3nj03338d
|View full text |Cite
|
Sign up to set email alerts
|

Single-phase excitation-wavelength-independent nitrogen doped graphene quantum dots for the fabrication of white light-emitting diodes (WLEDs)

Yue Xu,
Lubin Liu,
Miaojun Xu
et al.

Abstract: This research has developed single-phase solid-state white light N:GQDs, which not only replace the expensive and non-renewable rare earth resources, but also open up a new way for single-phase carbon-based quantum dots to realize WLED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…218 Recently, Xu et al utilized N-GQDs powder as a single emitter in LEDs to achieve WLEDs with CIE coordinates of (0.28, 0.31), a CCT of 7469 K, and a CRI of 92.3. 350 Yang et al have shown that by controlling solvent polarity and S-doping, the emission wavelength of GQDs can be adjusted from blue to red, and these multicolor GQDs can be used as the fluorescent layer in LEDs, resulting in a WLED with CIE coordinates of (0.341, 0.354) and a CCT of 5161 K. 351…”
Section: Applications Of Gqdsmentioning
confidence: 99%
“…218 Recently, Xu et al utilized N-GQDs powder as a single emitter in LEDs to achieve WLEDs with CIE coordinates of (0.28, 0.31), a CCT of 7469 K, and a CRI of 92.3. 350 Yang et al have shown that by controlling solvent polarity and S-doping, the emission wavelength of GQDs can be adjusted from blue to red, and these multicolor GQDs can be used as the fluorescent layer in LEDs, resulting in a WLED with CIE coordinates of (0.341, 0.354) and a CCT of 5161 K. 351…”
Section: Applications Of Gqdsmentioning
confidence: 99%